A New Energy Efficient and Reliable MedRadio Scheme Based on Cooperative Communication for Implanted Medical Devices - Jen-Ming Hsu; Tzu-Chiang Chiang; Yao-Chang Yu; Wei-Guang Teng; Ting-Wei Hou (International Journal of Distributed Sensor Networks)
The most significant shortcoming of implanted devices is the battery life. With advanced technology, implanted devices can have the capability to communicate with other health-related devices, but this also means the energy consumption requirement is greater than ever. Less power consumption would extend the duration of the batteries of implanted medical devices. In this paper, an energy efficient and reliable communication service device scheme that does not require any modification to the existing wireless network structure or the implanted devices under consideration is proposed. The scheme is intended to save a target device's energy necessary for resending communication signals by introducing a neighbor group header node and cooperative (wearable) nodes. The simulation results show that the scheme would result in energy savings of 70 percent with one or two cooperative nodes as compared with the current best approach.